Novel preparation of chiral 3, 2′-pyrrolidinyl spirooxindole from an enantioselective Michael addition between 3-(diphenylmethylene)-amino-oxindole and acrolein catalyzed by a cinchona alkaloid. (5th January 2022) - Huang, Zhi-Cheng; Xiang, Min; Li, Wen-Sheng; Zou, Ying; Li, Chen-Yi; Zhang, Jian; Li, Xia; Tian, Fang; Wang, Li-Xin
Graphical abstract: Highlights: Unique synthons. Extremely simple and mild reaction conditions. New chiral spirooxindole imine. Almost all the prepared chiral molecules with at least > 90%ee and final to 99%ee. The target molecule may be used as potential organocatalysts/ligands and potential new chemical entities. Abstract: A new type of spiro[pyrrolinyl-3, 2′-oxindole] scaffolds were effectively prepared from an enantioselective Michael/cyclization between a crucial synthon of 3-(diphenylmethylene)-amino oxindole and acrolein catalyzed by a cinchona alkaloid in up to 99% total yield with up to 99% ee. Those spirooxindole aldehyde imines were reduced to new kinds of prolineamide like spirooxindole chiral amine organocatalysts. The reaction has been successfully scaled up to a gram scale and most typical organocatalysts were further purified up to 99% ee by recrystallization in their hydrochloride salts.